Fluid replacement advice during work in fully encapsulated impermeable chemical protective suits - Rubenstein, Candace D.; DenHartog, Emiel A.; Deaton, A. Shawn; Bogerd, Cornelis P.; DeKant, Saskia (Journal of occupational and environmental hygiene, 2017)
A major concern for responders to hazardous materials (HazMat) incidents is the heat strain that is caused by fully encapsulated impermeable chemical protective suits. In a research project, funded by the US Department of Defense, the thermal strain experienced when wearing these suits was studied. One particular area of interest was the fluid loss of responders during work in these suits as dehydration may be an additional health concern to the heat strain. 17 City of Raleigh firemen and 24 students were tested at two different labs. Subjects between the ages of 25 and 51 were used for human subject trials in a protocol approved by the local ethical committee. Six different Level A HazMat suits were evaluated in three climates: moderate (24°C, 50% RH, 20°C WBGT), warm-wet (32°C, 60% RH, 30°C WBGT), and hot-dry (45°C, 20% RH, 37°C WBGT, 200 W/m 2 radiant load) and at three walking speeds: 2.5 km/hr, 4 km/hr, and 5.5 km/hr. 4 km/hr was tested in all three climates and the other two walking speeds were tested in the moderate climate. Weight loss data was collected to determine fluid loss during these experiments. Working time ranged from as low as 20 min in the hot-dry condition to 60 min (the maximum) in the moderate climate, especially common at the lowest walking speed. The overall results from all experiments showed that fluid loss ranged from 0.2-2.2 L during these exposures, with the average fluid loss being 0.8 L, with 56% of the data between 0.5 L and 1 L of fluid loss. Further analysis showed that a suggestion of drinking 0.7 Liter per hour would safely hydrate over 50% of responders after one work-rest cycle. Applying this fluid volume over three work-rest cycles only put 11% of responders at risk of hypohydration vs. the 57% at risk with no fluid intake.